Calculation of Atomic Spectroscopic Terms for Non-equivalent Electrons of f 2 d1 Configuration and Assigning the Term Symbols - Meena, P.L.; Kumar, N.; Meena, K.S.; Jain, P.K. (Asian Journal of Chemistry, 2012)
The term is a energy state, which arises from an approximation treatment of an electronic configuration and term symbol is label to that energy state. The importance of the term symbols have been emphasized in connection with the spectral and magnetic properties of complexes and metal free ions. Russell-Saunders (L-S) coupling and J-J coupling schemes are important schemes for determination of terms and term symbols of the atoms and ions. In this proposed work computation is done for calculating all possible terms for non-equivalent electron of f 2 d1 configuration without any long tabulation with mental exercise and term symbols are assigned the terms. The possible microstates and spectroscopic terms calculated for f 2 d1 configuration are 910 and 42 respectively. These terms are quartets (13) and doublets (29).The ground state term for f 2 d1 is 4K and the ground state is 4K11/2.